Hubungan Pengetahuan Gizi dan Asupan Zat Gizi Makro dengan Tingkat Kebugaran Jasmani Atlet Sepak Bola di SSB Ganesha Putra FC Purwodadi - Ulfatus Sa'adah; Angga Hardiansyah; Darmuin Darmuin (Universitas Mitra Indonesia, 2023)
Football athletes need good physical fitness. Fulfillment of macronutrient intake and knowledge of nutrients is important to consider in helping to increase the level of physical fitness of athletes. The study used a cross sectional design with a sample of 39 athletes. Macronutrient intake was obtained from the 3x24 hour recall intake interview, nutrition knowledge data was obtained from filling out the questionnaire questions, physical fitness data was obtained from the VO2 max test, the Multistage Fitness Test. Data analysis used Bivariate Gamma test analysis in the Statistical Package for the Social Science program. The majority of carbohydrate intake is less (56.4%), adequate protein intake (51.3%), low fat intake (48.7%), moderate nutritional knowledge (51.3%) and moderate physical fitness (53.8%). Then the Bivariate test analysis showed that carbohydrate intake (p = 0.024) had a relationship with physical fitness level because the p value 0.05, while protein intake (p = 0.084), fat intake (p = 0.072), and nutritional knowledge (p = 0.072). 0.107) has no relationship with the level of physical fitness. Carbohydrate intake can affect the level of physical fitness of athletes, so it is necessary to provide adequate intake of other nutrients to improve athlete fitness.